Exploring the hidden mental health consequences of malaria beyond the fever - Nandish, Prerana; B. M., Shrinivasa; N., Sujith Nath; Shankar, G.; Tripathi, Praveen Kumar; Kashyap, Himani; Jain, Animesh; Anvikar, Anup; Chalageri, Vani H. (Frontiers in Human Neuroscience, 2024)
Malaria morbidity has various presentations. The focus now shifts to uncommon signs and symptoms of malaria infection such as cognitive impairment to address the morbidity when the mortality declines. About 50% of children admitted to hospitals due to malaria experience neurological complications due to factors like low blood sugar, inflammation, elevated pressure, decreased oxygen levels, and excitotoxicity. Malaria during pregnancy negatively impacts children's cognitive, behavioral, and executive function leading to neurodevelopmental delay due to increased susceptibility which can significantly affect maternal and child health, leading to higher rates of underestimated factors like anxiety, depression, and PTSD. Despite having the world's second-largest tribal population, India's indigenous and tribal communities and their mental health are underdeveloped, and Western psychological tools are not universally applicable, necessitating the development of tailored tools to investigate malaria's link to psychological distress and evaluate intervention's effectiveness. This paper has illuminated the hidden mental health consequences of malaria infection, emphasizing the prevalence, nature, and implications of psychological distress among affected individuals. The findings underscore the importance of recognizing and addressing these psychological consequences in the holistic management and prevention of malaria and its mental health consequences.